ANALISIS PERILAKU KECURANGAN AKADEMIK PADA MAHASISWA AKUNTANSI DENGAN MENGGUNAKAN KONSEP FRAUD TRIANGLE (Studi pada Mahasiswa S1 Akuntansi Kota Malang) - Santoso, Muhamad Hadi; Adam, Helmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study examined the factors that influence the behaviour of students cheating by using the concept of fraud triangle consisting of pressure, opportunity and rationalization. This research using survey method in data collecting. This study received 136 responses of student from 12 college in Malang City and this research was analyzed using multiple linear regression analysis as an analysis model. The results of this study indicate that pressure, opportunity, and rationalization have an influence on students academic cheating behavior. Keywords : academic cheating, pressure, opportunity, rasonalisasi, accounting students.